Split Cord Malformation - A Diagnosis Missed - Nimrah Mairaj; Abdul Ali; Zainab Juzer (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
In this report, we describe the case of an 8 year old female child who presented with complaints of swelling in sacral region since birth and left leg weakness since 2 years of age. She presented with left clubbed foot to an orthopaedic surgeon and was treated at 1 year of age with serial plasters. The child was presented for club foot, rather than identifying the cause of deformity. When child was presented to our tertiary care hospital her workup was done and an incidental finding of split cord malformation on Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) myelogram was revealed along with left gluteal sebaceous cyst. The child underwent surgery and tethering of cord by the fibrous septa was relieved along with excision of left gluteal  sebaceous  cyst.  The  post-operative course was uneventful. Spinal cord malformations usually present with number of presentations  for  example hypertrichosis, lipoma, dermal sinus or tail. Therefore, a  thorough  examination  can  result  in early diagnosis of the malformation and the complications can be prevented. In our case hypertrichosis at the back was missed, prior to child being referred to us. Hence, this case is being reported as a diagnosis missed of split cord malformation due to lack of complete head to toe evaluation of child by a subspecialty expert.